Banking M&A value effects: European banks - Bahdanchuk, Victoria S.; Vasileuski, Anton V. (Journal of the Belarusian State University. Economics, 2018)
The aim of the article is to perform an empirical estimation of the aggregate effectiveness of the mergers and acquisitions with in European banking industry around the times of larger monetary regulatory changes. The relevance of the study is especially acute due to an increased liability of financial managers for facilitating stock growth and business expansion in the times of increasingly saturated market of financial services and the periods of significant changes in the state financial regulations. The analysis of the available stock quotes of the public companies will assist their managers in reducing the uncertainty when deciding on the acquisition of the competing companies, the expansion and strengthening the core businesses or diversifying into a new realm. The objects of the study are the European interbank mergers and acquisitions in the period from 1999 to 2016. The subject of the research is the economic effectiveness of European banking mergers and acquisitions described above. The analysis yields the following results: the effectiveness of mergers and acquisitions has been determined in the banking institutions industry depending on the choice of the target bank. The study presents the comparative numerical analysis of the transactions’ effectiveness at different times, split by the significant regulatory changes (Basel II, Basel III).
Keywords: M&A; mergers and acquisitions; value effects; European banks; event study; abnormal returns; cumulative abnormal returns